The reality for agricultural economics within the European Union : stressing the efficiency indicators across the representative farms - Martinho, Vítor João Pereira Domingues (SpringerBriefs in agriculture., 2017)
The objective of this study is to analyze several dimensions of the agricultural economics reality for the representative farms of the European Union countries by using microeconomic data available in the Farm Accountancy Data Network from 1989-2009. To support this research, several ratios and efficiency indicators were calculated across several variables relative, namely, to the agricultural output and the utilized agricultural area. These ratios and indicators were analyzed further through econometric models associated with the convergence approaches, presenting with more detail the Portuguese case. Furthermore, it is important to design a set of strategies that are more suited to the European Union realities.